A STUDY ON ONLINE MARKETING AND IT’S IMPACTS - Asharani. C (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Online marketing, which is also called internet marketing, involves use of interactive, virtual spaces for the sake of promoting and selling goods and services. Online Marketing is a combination of innovative tools and methodologies used for marketing products and services over the internet. Online marketing is the process of targeting, attracting and winning and retaining the potential customers through Internet. Online Marketing covers a wide range of marketing strategies which are excluded from traditional marketing because online marketing includes extra platforms and marketing mechanisms over the internet. Online marketing overcomes the barrier of traditional marketing i.e. reaching the mass with minimum cost. Online marketing helps the company to builds its brands online and to attract potential customers. Online marketing provides platform to companies to communicate with their customers and feedback given by the customers helps the company to easy work on their pitfalls and customers can make a wise decision of buying by analyzing the posted feedbacks on the company website. Being cost-effective, flexible, and fast and enjoying an on unprecedented global reach, internet marketing has brought about different businesses incredible gains. The paper study with defining online marketing, different kinds of internet marketing advantages and disadvantages of online marketing. This paper also examines how online marketing overcome the limitations of traditional marketing and study the challenges exist in India relating to Online Marketing: